The Effect of Information Technology on Employee Performance at the Makassar City Communication and Information Service - Darwis, Muh.; Utami, Nurislami Nanda; Saleh, Sirajuddin (Pinisi Journal of Education and Management, 2023)
The role of information technology in the bureaucracy can facilitate the implementation of tasks in information management, make work effective and efficient, and shorten service time so that performance becomes optimal. Information technology is currently based on the Internet of Thing (IoT) to support the acceleration of information, and in the government sector it is based on E-Government which supports data integration and can be accessed in real time within the Central Government and collaborating agencies. This study aims to describe information technology, employee performance and the influence of information technology on employee performance at the Makassar City Communication and Information Service. This research is an associative quantitative research which shows a causal relationship. Data collection techniques used are observation, questionnaires and documentation. The data analysis technique used is descriptive statistical analysis and inferential statistics. The test results show that the variables of information technology and employee performance are in a very good category, based on the product moment correlation test, the relationship between variables is very strong. Based on the results of simple linear regression analysis it was concluded that there is a positive and significant influence of information technology on employee performance at the Makassar City Communication and Information Service.